TREM2 Binds to Apolipoproteins, Including APOE and CLU/APOJ, and Thereby Facilitates Uptake of Amyloid-Beta by Microglia - Yeh, Felix L.; Wang, Yuanyuan; Tom, Irene; Gonzalez, Lino C.; Sheng, Morgan (Neuron (Cambridge, Mass.), 2016)
Genetic variants of TREM2, a protein expressed selectively by microglia in the brain, are associated with Alzheimer’s disease (AD). Starting from an unbiased protein microarray screen, we identified a set of lipoprotein particles (including LDL) and apolipoproteins (including CLU/APOJ and APOE) as ligands of TREM2. Binding of these ligands by TREM2 was abolished or reduced by disease-associated mutations. Overexpression of wild-type TREM2 was sufficient to enhance uptake of LDL, CLU, and APOE in heterologous cells, whereas TREM2 disease variants were impaired in this activity. Trem2 knockout microglia showed reduced internalization of LDL and CLU. β-amyloid (Aβ) binds to lipoproteins and this complex is efficiently taken up by microglia in a TREM2-dependent fashion. Uptake of Aβ-lipoprotein complexes was reduced in macrophages from human subjects carrying a TREM2 AD variant. These data link three genetic risk factors for AD and reveal a possible mechanism by which mutant TREM2 increases risk of AD. [Display omitted] •TREM2 binds to lipoproteins and apolipoproteins including APOE and CLU•Disease-linked mutations in TREM2 impair lipoprotein binding and uptake into cells•Aβ-lipoprotein complexes are efficiently taken up by microglia, dependent on TREM2•Human carriers of a TREM2 AD variant show reduced uptake of Aβ-lipoprotein complexes Yeh et al. show that TREM2 is a receptor for lipoproteins, including APOE and CLU, and thereby mediates uptake of lipoprotein-Aβ complexes by microglia. The study links together three genetic risk factors of Alzheimer’s disease and offers new insight into the mechanisms of Aβ clearance.